Positioning Control System on the Movement of Wheeled Humanoid Robot Using Swerve Drive Model Based on Fuzzy Logic Controller - Harry, Caroline; Amirulsyah, Ahmad Rizky; Hermawati, Harmawati; Dwijayanti, Suci; Suprapto, Bhakti Yudho (Universitas Syiah Kuala, 2025)
Technology in robotics has developed rapidly in the last few decades, as evidenced by the increasing number of robots created, such as humanoid robots and mobile robots. In this study, a wheeled humanoid robot is designed to move from one place to another using a swerve drive model, a holonomic type of drive wheel. This model uses a combination of DC motors and gears to ensure smooth movement of the humanoid robot. The swerve drive allows the robot to move freely in all directions. Therefore, the humanoid robot requires a control system to manage and automatically regulate the state of the system. The fuzzy logic control system can perform mathematical calculations based on human knowledge, serving as a controller without requiring a mathematical model of the controlled process. The results obtained from this study demonstrate the robots ability to move stably and accurately, based on the response to the rules provided by the fuzzy logic control system. The more membership functions used, the more stable and accurate the results will be, while using fewer membership functions will result in faster response times to reach the setpoint.